The Relationship Between Transformational Leadership, Leader Effectiveness, and Turnover Intentions: Do Subordinate Gender Differences Exist? - Wells, Janelle E.; Peachey, Jon Welty; Walker, Nefertiti (Journal of Intercollegiate Sport, 2014)
The aim of this study was to examine gender differences among subordinates in the strength of relationships between transformational leadership, leader effectiveness, and voluntary organizational turnover intentions. The authors drew from various theoretical bases, including transformational leadership theory, social role theory, and role congruity theory, to undergird the research. National Collegiate Athletic Association (NCAA) Division I male and female assistant coaches of women’s basketball, softball, and volleyball teams (N = 294) responded to the Multifactor Leadership Questionnaire (MLQ) and turnover intention questionnaire. Structural equation modeling (SEM) revealed a noteworthy gender difference in the strength of relationship between leader effectiveness and voluntary organizational turnover intentions. Contributions and implications are discussed.